Gustatory Dysfunction among a Sample of Depressed Egyptian Adults under Antidepressants Therapy: A Retrospective Cohort Study - Christine Mikhail; Khaled Elgaaly; Ahmed Abd El Latif Abd El Hamid; Olfat Shaker; Shereen Ali (Hindawi Limited, 2021)
It is quite clear that the ability to perceive taste sensations significantly affects food choice, which consequently affects health status in the long term. Gustatory dysfunction is a neglected symptom among the depressed patients and those under antidepressants therapy, although these patients are suspectable to oral problems, due to general self-negligence related to mental disease, fear of dental treatment, and side effects of varied medications utilized in psychiatry. This study is aimed at assessing gustatory thresholds (detection and recognition thresholds) among a sample of 30 depressed Egyptian adults under antidepressants therapy for at least 3 months or psychotherapy with age ranging from 20 to 50 years old, seeking the Psychiatric Clinic at the Faculty of Medicine, Cairo University, Egypt. These patients were distributed into three equal groups (tricyclic antidepressants (TCA), selective serotonin reuptake inhibitors (SSRIs), and psychotherapy) and were assessed for gustatory detection and recognition thresholds using the filter paper disc method through a scoring system. The participants were also divided into normal taste group in which both the detection and recognition scores were 1, while the scores from 2 till 5 were considered as hypogeusia group and the score of 6 was considered as dysgeusia group. The TCA group was statistically significant from the other 2 groups in sweet detection thresholds (p = 0.043) and sweet recognition thresholds (p = 0.007). Hypogeusia for sweet was statistically significant (p = 0.041), where it was more common among TCA (70%) than both SSRIs and the psychotherapy group (20%). Gustatory dysfunction was found to be mostly associated with TCA followed by SSRIs particularly for sweet taste thresholds. More attention has to be given to taste changes among these patients as oral health affects general health by causing considerable pain and by changing what people eat, their speech, and their quality of life and wellbeing. Proper awareness and evaluation of this problem will improve the quality of life for the depressed patients and avoid unnecessary treatment. This trial is registered with ClinicalTrials.gov ID: NCT03599011.